Pathogenicity and Distribution of Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus in Pigs. Issue 4 (5th July 2012) - Hu, S. P.; Zhang, Z.; Liu, Y. G.; Tian, Z. J.; Wu, D. L.; Cai, X. H.; He, X. J.
Summary The pathogenesis of highly pathogenic porcine reproductive and respiratory syndrome virus (PRRSV) strain (HuN4) is poorly understood. Therefore, highly pathogenic PRRSV strain (HuN4) and its derivative strain (HuN4‐F112) (obtained by propagation in MARC145 cells for 112 passages) were inoculated into a total of 48 PRRSV‐sero‐negative pigs (age: 4–5 weeks) by the intranasal route. Virological, pathological and in situ hybridization analyses were performed. The results exhibited that pigs infected with HuN4 showed a loss of appetite, decrease in body weight, raised body temperature and respiratory symptoms, along with interstitial pneumonia lesions. In the HuN4 group, multifocal interstitial pneumonia with macrophage infiltration was found in the lung. The lesions in the lymph node were characterized by collapsed follicles, depletion of germinal centres and reduction in lymphocytes. Perivascular cuffing and glial nodules were observed in the brains of some pigs. By comparison, the HuN4‐F112 group had milder lesions. PRRSV was detected in macrophages, alveolar epithelial cells and vascular endothelial cells in the tonsil and lymph nodes. The PRRSV amounts in the pigs infected with HuN4 were 105–109 copies/ml in the blood and 1010–1011 copies/g in the lung tissues, whereas the virus amounts with HuN4‐F112 were 102.15–103.13 copies/ml in the blood and 103.0–103.6 copies/g in the lung. Our results demonstrate that the PRRS HuN4 virus infects alveolar epithelial cells, macrophages and vascular endothelial cells causing diffuse alveolar damage and lymph node necrosis. Its higher pathogenicity compared with HuN4‐F112 virus may be explained in part by higher replication rate in the previously mentioned organs.